The Era of Emotional Marketing - Dhannur, Vijaykumar (SFIMAR Research Review, 2011)
Human beings are all emotional creatures; they have deep rooted need to connect with one another and the world around them. In a competitive world with increasing difficulty in differentiating the products from its competitors, marketers are now realizing the need to discover a new ground to compete - on which the emergence of the Emotional Marketing has largely stemmed from this need. The goal of emotional marketing is to build an enduring bond with customers that cultivate loyalty and there by stimulate repeat purchase. Emotion acts as a catalyst in the engine of the purchase decision process. Customers need an unprecedented level of emotional commitment and honesty from the brands they trust, support and buy. By identifying customer needs, wants and aspirations marketers can create buying experiences, which generate frequent buying patterns, buying relationships and loyalty. Maslow's theory is an exceptional framework for successful marketing efforts. Each sale not only sells a concrete product but also an abstract view of the same, such as its prestige or the change it will help the consumer achieve. The more level of Maslow's hierarchy a product seems to satisfy, more successful the marketing efforts will be for that product. Any successful marketing campaign must first focus on what consumer motivators they will target. It's important to figure out where in the hierarchy of needs the wants of the customer would fit in. Emotional Marketing principles lead to strategies that are almost impossible to replicate, providing a powerful competitive advantage. This paper unravels the application of emotional marketing as a strategic tool by developing a holistic theoretical model by integrating both Maslow's need theory and emotional marketing. This integrated approach can help marketers to achieve sustainable competitive advantage and in driving long term loyalty.